Common developmental trajectories and clinical identification of children with fetal alcohol spectrum disorders: A synthesis of the literature - Douglas Waite; Larry Burd (Frontiers Media S.A., 2023)
At an estimated prevalence of up to five percent in the general population, fetal alcohol spectrum disorders (FASD) are the most common neurodevelopmental disorder, at least if not more prevalent than autism (2.3%). Despite this prevalence in the general population, pediatricians and other developmental specialists have thus far failed to diagnose this disability, leaving most children and adults without the supports provided for most other disabilities. This paper will provide a review of clinically relevant literature that describes the developmental challenges of children with fetal alcohol spectrum disorders and addresses similarities to and differences of FASD from other neurodevelopmental disorders such as autism and attention deficit hyperactivity disorder. A subsequent discussion will describe how a diagnosis of an FASD can establish a basis for understanding the developmental and behavioral challenges of children with an FASD, and how specific interventions can help support child development and maximize adult independence.